Programa "Jugando en los sectores" para desarrollar capacidades matemáticas en niños de 4 años de una institución educativa del Callao - Salas Jaramillo, Ana Doris (2012)
The present research was intended to establish the usefulness of the “Playing in the Classroom Zones” program to improve the development of math capabilities of number and relationship in four-year-old children, specifically in the dimensions of quantity and classification, counting and order. It is a quasi-experimental research where the pretestpostest design has been used jointly with a control group. The samples were composed by 24 children belonging to the control group and 24 children belonging to the experimental group, in which the program was applied from September to November 2011 in an educational institution of Callao. For data collection, it was necessary to apply the Math Capabilities Test for four-year-old children in early childhood education (CAM I-4, due to its abbreviations in Spanish) which was submitted to validation through experts’ opinions and has an adequate level of reliability to .919. The results conclude that there are significant differences in math capabilities in the group, in which the “Playing in the Classroom Zones” program was applied compared to the other one in which the program was not applied.